2002
DOI: 10.1001/archfaci.4.1.8
|View full text |Cite
|
Sign up to set email alerts
|

The Versatility of Distraction Osteogenesis in Craniofacial Surgery

Abstract: To review our preliminary results using distraction osteogenesis for the correction of craniofacial deformities and to determine its role in treating anatomic deformities and functional deficits relative to conventional craniofacial surgery.Design and Setting: Retrospective clinical review; tertiary care center.Methods: Twenty-four consecutive patients were treated with distraction osteogenesis during a 34-month period. Outcomes were compared with preexisting anatomic deformities and functional deficits using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…This choice is based on the results of Richardson et al [44] who observed an exponential increase in stiffness during tibial fracture healing. The period of 75 days was chosen based on an average of times reported for the consolidation and the calcification of the fracture callus [13,27]. The same time scale was set for all tissue types, however in reality one might expect different rates to apply to different tissues.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This choice is based on the results of Richardson et al [44] who observed an exponential increase in stiffness during tibial fracture healing. The period of 75 days was chosen based on an average of times reported for the consolidation and the calcification of the fracture callus [13,27]. The same time scale was set for all tissue types, however in reality one might expect different rates to apply to different tissues.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, too long a latency period may substantially increase the risk of premature bone union [27], which can hinder the subsequent expansion process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When compared to conventional mandibular surgery, this method of bone lengthening in the treatment of hypoplastic mandibular ramus due to hemifacial microsomia 23) and bilateral mandibular distraction in the treatment of micrognathia 20) is less invasive and can be performed before the end of the growth period, thus reducing psychological stress 13) . Moreover, smaller screws that can be placed in the oral cavity have recently been made, and such screws are being more widely used 14,22) .…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies in dogs demonstrate regeneration of the mandibular canal containing both neural and vascular elements. However, the functional level of the regenerated neurovascular structures is less than normal (Imola et al, 2002;Imola et al, 2008).…”
Section: Distraction Osteogenesismentioning
confidence: 96%